PENGARUH PROGRAM MEMBER GET MEMBER TERHADAP PENINGKATAN JUMLAH MURID DI biMBA AIUEO GADJAH MADA PURWOREJO (STIE Rajawali Purworejo, 2021)
The aim of this research is to determine the effect of the member get member program on increasing the number of students at biMBA AIUEO Gadjah Mada Purworejo. Data collection techniques in this research were obtained by observation, interviews, literature study and documentation. This research is included in descriptive qualitative research. The data analysis technique used in this research uses the instrument test used, namely simple linear regression analysis, coefficient of determination, and partial testing (t test). The results of the simple regression analysis are Y = 36.919 + 0.781 points, then the variable size for increasing the number of students is 0.781. The results of the calculation of the coefficient of determination show that R2 is 96.2% for the dependent (dependent) variable, namely the increase in the number of students. The remaining 3.8% increase in student numbers was influenced by other variables such as free registration promotions, coloring competitions and reading performances. The t test results obtained thitung is greater than ttabel (250.035> 2.228) and the significant level is (0.000 < 0.05) so Ho is rejected and Ha is accepted, which means there is a positive and significant influence on the member get member program variable towards increasing the number of students at biMBA AIUEO Gadjah Mada Purworejo.